STRATEGI GURU BK DALAM MENGATASI MISSBEHAVE DI SEKOLAH: STUDI KASUS DI SMK NEGERI 3 KOTA SORONG - Aryadhy, Aryadhy; Nurfitriani, Nurfitriani; Masseni, Masseni (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2026)
Student conflict is an inseparable phenomenon from the dynamics of school life, especially in vocational high schools that have complex social characteristics and student development. This study aims to analyze the strategies of Guidance and Counseling Teachers (BK) in overcoming deviant student behavior conflicts at SMK Negeri 3 Kota Sorong, as well as to identify the challenges faced in implementing these strategies. This study uses a qualitative approach with a case study design. The research subjects were determined purposively, including guidance and counseling teachers and students involved in conflicts. Data collection techniques were conducted through in-depth interviews, observation, and documentation, while data analysis used the interactive model of Miles, Huberman, and Saldana with triangulation techniques to ensure data validity. The results showed that guidance counselors applied conflict management strategies in a gradual and integrated manner, with individual counseling as the initial strategy to understand students' problems on a personal level. Subsequently, group counseling, mediation, and character building were used as follow-up measures in accordance with the characteristics of the conflict. However, the effectiveness of these strategies was influenced by the limited number of guidance counselors, the diverse social backgrounds of students, and the resistance of some students to counseling services. This study concludes that handling student conflicts in vocational high schools requires adaptive, systematic guidance counseling services supported by the school's comprehensive role in order to create a conducive and sustainable educational climate.